2004
DOI: 10.1212/01.wnl.0000138438.88589.7c
|View full text |Cite
|
Sign up to set email alerts
|

Cosmetic neurology

Abstract: Advances in cognitive neuroscience and neuropharmacology are yielding exciting treatments for neurologic diseases. Many of these treatments are also likely to have uses for people without disease. Here, I review the ways in which medicine might make bodies and brains function better by modulating motor, cognitive, and affective systems. These potential "quality of life" interventions raise ethical concerns, some related to the individual and others related to society. Despite these concerns, I argue that major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(47 citation statements)
references
References 46 publications
2
42
0
3
Order By: Relevance
“…These physicians are sometimes asked to prescribe for enhancement by patients who exaggerate or fabricate symptoms of ADHD, but they also receive frank requests, as when a patient says "I know I don't meet diagnostic criteria for ADHD, but I sometimes have trouble concentrating and staying organized, and it would help me to have some Ritalin on hand for days when I really need to be on top of things at work. " Physicians who view medicine as devoted to healing will view such prescribing as inappropriate, whereas those who view medicine more broadly as helping patients live better or achieve their goals would be open to considering such a request 22 . There is certainly a precedent for this broader view in certain branches of medicine, including plastic surgery, dermatology, sports medicine and fertility medicine.…”
Section: Maximum Benefit Minimum Harmmentioning
confidence: 99%
“…These physicians are sometimes asked to prescribe for enhancement by patients who exaggerate or fabricate symptoms of ADHD, but they also receive frank requests, as when a patient says "I know I don't meet diagnostic criteria for ADHD, but I sometimes have trouble concentrating and staying organized, and it would help me to have some Ritalin on hand for days when I really need to be on top of things at work. " Physicians who view medicine as devoted to healing will view such prescribing as inappropriate, whereas those who view medicine more broadly as helping patients live better or achieve their goals would be open to considering such a request 22 . There is certainly a precedent for this broader view in certain branches of medicine, including plastic surgery, dermatology, sports medicine and fertility medicine.…”
Section: Maximum Benefit Minimum Harmmentioning
confidence: 99%
“…Modafinil is believed to increase concentrations of glutamate and decrease GABA within the posterior hypothalamus, producing an overall neuro-excitatory effect (Ferraro et al, 1999). The drug has been shown to improve attention and working memory in medical practitioners and aviators and may be used in other challenging professions (Turner et al, 2003; Chatterjee, 2004; Müller et al, 2004; Walsh et al, 2004; Czeisler et al, 2005; Warren et al, 2009; Garcia et al, 2013). …”
Section: Nootropic Agents and Evolutionmentioning
confidence: 99%
“…Keywords: bioethics, cognitive enhancement, neuroethics, psychopharmacology, attention deficit disorder/ADHD, depression Over the last 10 years, issues about cognitive enhancement 1 (CE) have been widely discussed in the academic literature (e.g., Bostr€ om and Sandberg 2009;Cakic 2009;Chatterjee 2004;de Jongh et al 2008;Farah et al 2004;Hildt and Franke 2013;Maher 2008;Sahakian and MoreinZamir 2011;Schermer et al 2009) as well as in the media. The controversy can be viewed as consisting of two interrelated topics.…”
Section: Target Articlementioning
confidence: 99%
“…2 These cognitive capacities increase people's ability to solve mental and intellectual problems and thereby make them "smarter" or more intelligent. The prospect of making healthy and normal functioning people "smarter," within a relatively near future, by means of CES, sparked the debate on ethical issues such as concerns about equal access, (in)equality, transgressing the bounds of medicine, cheating, cognitive liberty, coercion, and authenticity (e.g., Chatterjee 2004;Farah et al 2004;Fukuyama 2002). However, literature reviews on the socalled CES report that many studies have found no or only modest effects on most cognitive capacities-especially in individuals already functioning at normal or high levels (Lucke et al 2011;Outram 2010;Repantis et al 2010;Smith and Farah 2011).…”
Section: Target Articlementioning
confidence: 99%